Electron beam generation in a low-impedance system - Agafonov, A.V. (Вопросы атомной науки и техники, 2006)
Results of computer simulation of low-energy high-current electron beam generation in a low-impedance system consisting of plasma-filled diode with a long plasma anode, an auxiliary thermionic cathode, and an explosive emission cathode are given. The auxiliary cathode is used to form the long plasma anode by means of residual gas ionization by a low-current low-voltage electron beam (currents of amperes, voltage of hundred volts) in an external longitudinal magnetic field. The high-current low-energy electron beam (currents of tens kA, voltage of tens kV) is generated from the explosive emission cathode embedded in prepared plasma. The long plasma anode presents simultaneously a transport channel providing charge neutralization of high-current beam. Computer simulation is performed using PIC code KARAT for different geometry and position of auxiliary cathode. Computer results are compared with experimental data. Work supported by RFBR under grant 05-02-16442.